Analisis Kemampuan Toleransi Sosial pada anak usia 5-6 tahun di TK Telkom Gorontalo - Amalia Monoarfa; Amelia Daaliwa; Cindawati Pakaya; Triassetiawaty Dade; Fiola Indah Putri Pratama (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
Introducing a sense of tolerance from an early age, especially in preschool, is crucial for building a harmonious society. This article discusses the importance of instilling the values ​​of tolerance and mutual respect among children, particularly in the context of religious diversity. The study, conducted at Telkom Kindergarten in Gorontalo, involved seven students aged 5-6 years. The data collection technique used a Guttman scale questionnaire with intervals (Yes-No). The results showed that 85% of children had demonstrated tolerant attitudes, which include accepting differences, respecting others, and appreciating the religion or beliefs of others. However, there were still 15% of children who were not fully tolerant. Therefore, it is recommended to further develop social tolerance skills in early childhood through various structured and systematic approaches, such as modeling, habituation, storytelling, outdoor activities, singing, and providing appropriate rewards and consequences. It is important to build strong synergy between parents and teachers in formal educational institutions to guide children in developing a tolerant character. In addition, efforts need to be made to increase students' awareness of good behavior, and parents' use of democratic education also plays a crucial role in developing tolerance skills in early childhood.